(untitled) (Research, Society and Development, 2020)
The objective of this study was to evaluate the effect of two distinct soils on the productive, morphogenic and structural characteristics of two cultivars of Brachiaria brizantha. The experiment was conducted in a completely randomized design with three replications. The treatments consisted of two cultivars (Piatã and Marandu) and two soils (Cambissolo and Argisolo), in a 2 x 2 factorial arrangement. There was no interaction (P>0.05) between the factors. Soil type and cultivar did not affect (P>0.05) the morphogenic and structural characteristics of the grasses. There was an effect (P<0.05) of soil type and cultivar on forage yield characteristics. Plant height and dry matter yield were higher in Cambisol (28.37 cm and 4.31 g/pot, respectively). Among cultivars, the highest height was observed in piatã grass (27.0 cm), while marandu grass showed higher tillering (20.33 tillers/pot). Tiller population density and leaf/stem ratio were not affected (P>0.05) by soil type. Grasses had higher growth and were more productive when grown in Cambisol. The cv. Marandu presented higher tillering in detriment of the smaller growth in height in relation to the cv. Piatã.